PENGARUH SISTEM PELAYANAN PAJAK DAN KEPATUHAN WAJIB PAJAK ORANG PRIBADI TERHADAP PENERAPAN SELF ASSESSMENT SYSTEM DI KANTOR PELAYANAN PAJAK PRATAMA BANTUL - Uum Helmina Chaeurnisak; Suyanto Suyanto (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2014)
This study was conducted to examine the effect of the tax system variables and individual tax compliance on the implementation of self assessment system in KPP Pratama Bantul. This study uses the dependent variable is self assessment system and the indepen dent variable is the tax system , an individual taxpayer compliance are listed in the KPP Pratama Bantul. The sampling technique used is random sampling of individual taxpayers in the region of Bantul and individuals who have a NPWP. Data collection procedures using a questionnaire which was distributed to be filled by an individual taxpayer. The analysis technique used is multiple regression with SPSS 16.0 tools. Based on the results of the analysis indicate that the variable tax system and compliance services an individual taxpayer simul tan proved significant effect on the implementation of self assessment system . Predictive ability of the three variables on self assessment system shows the independent variables can explain the variation in the dependent variable of 34.8 % and the rest is explained by other variables. Keywords: system of service tax, individual tax compliance, and self assessment system .